Nurses' Knowledge Level of Early Warning Score (EWS) in the Internal Medicine Room of Santa Elisabeth Hospital Medan - Indra Hizkia Perangin-angin; Rusmauli Lumban Gaol; Sry Rumondang Sitindaon; Putri Rista Ulina Br Tarigan (Pusat riset dan Inovasi Nasional, 2025)
Early Warning Score (EWS) is a useful assessment system for monitoring and detecting patient conditions before they worsen, so that appropriate decision-making can be made, including referring patients and providing interventions as needed. The purpose of this study was to determine the Level of Knowledge of Early Warning Score (EWS) Nurses in the Internal Medicine Room of Santa Elisabeth Hospital Medan in 2025. The research method used was descriptive. A population of 94 people was taken professionally. The results of the study showed the Level of Knowledge of EWS Care in the Internal Medicine Room of Santa Elisabeth Hospital Medan in 2025 Based on the Definition of Respondents More Category Sufficient as many as 2 People (2.1%), Based on Indications for Use of EWS Number of Respondents More Category Less overall 3 People (3.2%), Category Sufficient as many as 48 people (51.1%), Based on Physical Parameters in EWS Respondents More Category Less than 4 People (4.3%), Category Sufficient as many as 23 people (24.5%), Based on EWS Assessment Number of Respondents More Category Less as many as 1 Person (1.1%), Category Sufficient as many as 70 people (74.5%), Based on the Role of Nurses in EWS Number of Respondents More Category Less as many as 7 People (7.4%), Category Sufficient as many as 49 (52.1%), Based on EWS Standardization Number of Respondents More Category Less overall 17 People (18.1%), Category Sufficient as many as 45 people (47.9%). Conclusion Level of Nurses' Knowledge of Early Warning Score (EWS) at Santa Elisabeth Hospital Medan in 2025 knowledgeable with 94 respondents showed that nurses with sufficient knowledge were 39 respondents (41.5%), and nurses with good knowledge were 39 respondents (58.5%). It is recommended that Santa Elisabeth Hospital Medan organize or conduct training workshops on the use of EWS.